THE EFFECTIVENESS OF CLASSROOM MANAGEMENT IN ENGLISH LANGUAGE TEACHING AND LEARNING FOR TENTH GRADERS OF SMA PANJURA MALANG - ASTUTI, AGRIT DWI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: effective classroom, classroom management, English language teaching, tenth graders students of Senior High School. English is international language that should be learnt by people in every country, included Indonesia. Effective English language teaching and learning process was needed for students in Indonesia. Whether classroom is effective to support teaching and learning process was influenced by many factors such as teaching strategy, managing classroom and students themselves. The writer uses 4 instruments to measure the effectiveness of classroom external and internal. The writer uses observation form, interview guide and field note. Observation form that use adapted from Burden (1995) Teaff (2007). For interview guide the writer prepares 10 questions related to classroom management. The subjects of this study are the English teacher of X IPS 4 and 33 students of X IPS 4. The objective of this study is to find out how to manage classroom, teaching strategies and student behavior to create effective classroom. This study uses descriptive qualitative research. The writer conducts the observation 3 times and 1 time interview guide for the English teacher of X IPS 4. The result of the study reveal that 5 aspects that being analyzed from observation form, they are physical arrangement, instructional time, instructional strategies, behavioral consideration, and social climates are fulfill completely.  The classroom management of X IPS 4 SMA Panjura Malang is effective enough to support teaching and learning process. The observation shows that the teacher has authoritative characteristic. Based on the study, the writer suggested that teacher should have various methods, strategies and media to increase students' motivation. Teacher should play as main role for students. Teacher should have patient to face students, but if they over patient it can make students not serious during learning process.